Analysis and optimization of folding-boom arm system luffing stability. (3rd July 2020) - Xu, Jun; Weng, Qimeng; Wu, Jingbin
Abstract: In order to guarantee stability during luffing process of a folding-boom arm system, output of the system should be precisely controlled based on analysis of key factors affecting luffing stability. Luffing motion was simulated focusing on jittering of the working point at beginning and end moment. Simulation results indicate that luffing stability is mainly determined by the action synchronization of hydraulic cylinders which drive the middle arm. An optimal control strategy was proposed through parameter adjusting. The field test results have shown the luffing stability is improved. Meanwhile, the requirement on executive precision of hydraulic cylinders has also been greatly reduced.